Fractional calculus to control transport phenomena in food engineering: A systematic review of barriers and data agenda - Matias, Gustavo de Souza; Lermen, Fernando Henrique; Bissaro, Camila Andressa; Nicolin, Douglas Júnior; Fischer, Clovis [UNESP]; Jorge, Luiz Mário de Matos (Wiley, 2022)
This study aims to conduct a systematic review of the literature through bibliometrics and content analysis to raise barriers, data agenda, and a framework to support academics and practitioners of fractional calculus in transport phenomena from the perspectives of food engineering. The structure of the methodological procedure is a selection of studies in the research area, statistical analysis of the data, and content analysis. The Bibliometrix package of software R was used in the bibliometric analysis, being fundamental for the organization of the discussions. Finally, the food engineering area researchers can use the questions, barriers, and research agenda in fractional calculus to solve problems in the studied clusters' processes. Based on the previous knowledge of the researcher, a path was provided to follow the data agenda and the proposed framework, identify insights, and solve a specific problem. As the main contribution, this study presents several applications and the most significant barriers and presents bibliometrics quantifying the theoretical and empirical studies in the area. Nonetheless, this study places the research field of fractional calculus for Food Engineering, Science, and Technology, presenting several applications and the most significant barriers quantifying the theoretical and empirical studies in the area. As a practical contribution, this study presents a research agenda and a framework that can contribute to practitioners applying fractional calculus in process control.
Keywords: food engineering; food process control; fractional calculus; fractional derivatives; math modeling